Translating the Biblical Hebrew Word Nephesh in Light of New Research. Issue 2 (August 2019) - Pleijel, Richard
In this paper, the translation of the Biblical Hebrew word nephesh is discussed in light of new research. The starting point for the paper is a 1976 article in The Bible Translator that discusses the translation of nephesh based on the idea that it is a monistic entity referring to human beings as such. It is shown that this view was most representative for the exegetical consensus of the time of the article. However, a fair amount of new research points out new directions for interpreting nephesh as an entity or essence that was perceived as being separable from the body. This is also confirmed by research on cognate ancient Near Eastern concepts. It is argued that this should affect our way of translating the word nephesh .